Evaluation of atopy schools for parents - García-Soto, Laura; Martin‐Masot, Rafael; Espadafor-López, Beatriz; Martínez Cañavate-Burgos, Ana María; Tercedor-Sánchez, Jesús (Codon Publications, 2021)
Introduction: Atopic dermatitis is a highly prevalent chronic disorder. Therapeutic education in diseases of this kind is essential in order to improve patient management and prognosis. A study was conducted regarding parent satisfaction following educational sessions in an Atopy School organized by a multidisciplinary team. Material and methods: E-mail surveys with variables scored by means of a Likert scale were administered among the parents participating in the workshops organized by the Atopy School. The educational program comprised four sessions with a duration of 4 hours. Results: Ninety-five percent of the parents were satisfied after participating in the workshops, and were of the opinion that the therapeutic education received was useful for improving control of the illness of their children. Likewise, 85% were satisfied or very satisfied with the help received in the sessions for control of the disease during flare-ups, and 90% considered the data and advice received in the sessions to be of use in improving quality of life of both the children and the family as a whole. Conclusions: The Atopy School afforded caregiver empowerment, and the parents were satisfied and felt more secure in dealing with the disease of their children-thereby improving the prognosis and quality of life.
Keywords: Dermatitis de contacto; Atopy School therapeutic education; atopic dermatitis